2016
DOI: 10.1007/s12250-016-3721-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphism rs2065955 of the filaggrin gene with susceptibility to Epstein-Barr virus-associated gastric carcinoma and EBV-negative gastric carcinoma

Abstract: The relationship between the Filaggrin gene (FLG) rs2065955 polymorphism and susceptibility to Epstein-Barr virus (EBV)-associated gastric carcinoma (EBVaGC) and EBV-negative gastric carcinoma (EBVnGC) was investigated in Shandong Province, China. We detected the FLG rs2065955 genotype and allele distribution by using PCR and restriction fragment length polymorphism (RFLP) in 64 EBVaGC, 82 EBVnGC, and 111 normal control samples. Immunohistochemistry was used to detect the level of FLG protein in 35 EBVaGC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The genotype AA of rs3126085 (c.3321delA), as a most popular FLG mutation in Chinese Han people, was considered as a hazardous sign for EBV-associated gastric carcinoma ( Yang et al, 2017 ). Another study detected the FLG rs2065955 genotype and allele distribution in 64 EBV-associated gastric carcinoma samples, and found genotype CC may contribute more to the risk of developing EBVaGC ( Kuang et al, 2016 ). Nevertheless, no significant difference in FLG expression was detected by immunohistochemical analysis in those studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotype AA of rs3126085 (c.3321delA), as a most popular FLG mutation in Chinese Han people, was considered as a hazardous sign for EBV-associated gastric carcinoma ( Yang et al, 2017 ). Another study detected the FLG rs2065955 genotype and allele distribution in 64 EBV-associated gastric carcinoma samples, and found genotype CC may contribute more to the risk of developing EBVaGC ( Kuang et al, 2016 ). Nevertheless, no significant difference in FLG expression was detected by immunohistochemical analysis in those studies.…”
Section: Resultsmentioning
confidence: 99%
“…These keratinocytes act as a matrix in the stratum corneum. A previous study has shown that FLG gene mutations possibly bring about a greater susceptibility to Epstein–Barr virus (EBV)–associated gastric carcinoma ( Kuang et al, 2016 ). This may be related to the fact that about 9% of gastric cancers harbor EBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In a targeted gene approach study, a comparison of 30 EBV+ cases to 120 EBV-negative cases revealed an association for promoter polymorphisms at the TNF-α and IL-10 gene loci [ 201 ]. Additional targeted approach studies revealed associations with Filaggrin (FLG), a filament-associated protein that binds to keratin fibers, in EBV+ GC, and EBV-negative GC [ 202 ]. Glypican-4 (GPC4), a member of the heparan sulphate proteoglycan family, was associated with EBV+ GC [ 203 ].…”
Section: Susceptibility To Ebv-associated Malignanciesmentioning
confidence: 99%
“…SNPs have been the focus of much interest and debate in recent years regarding their possible role in the development of various types of cancer (Wu et al, 2013). It is widely accepted that the signifi cant SNPs can be used as biomarkers for diagnosis and to evaluate the risk and prognosis of some diseases including cancers (Pipan et al, 2015;Xu et al, 2015;Kuang et al, 2016). However, there is little information available in literature about PPP1R15A gene polymorphism.…”
Section: Introductionmentioning
confidence: 99%